(3GdGSJKeGQ GdRQGYj SHjd dJMbjb GdCef GdZPGFj (B:s (3GdLRGFQ QDjI GSJQGJjLjI (B/s - (3SYjL, ehfjQI s ((3GdLRGFQ(B: s (3OGQ CLjGd GdQbej (B, s, 2024)
(3jJfGhd GdcJGH JWhQ GdCgejI GdGSJQGJjLjI ddbWGY GdRQGYj hJCKjQ GdGSJKeGQ Ydi eMGhQ GdCef GdZPGFj aj GdLRGFQ NdGd GdaJQI(B2000-2017(3, QDjI GSJQGJjLjI fMh JaYjd GdGSJKeGQ GdRQGYj dJMbjb GdCef GdZPGFj aj GdLRGFQ(B. s
(3HjHdjhZQGajG(B: (3U U(B.131-132s
Keywords: (3GdGSJKeGQs; (3GdCef GdZPGFjs; (3GdRQGYI (B-(3GbJUGOjGJ s